MATHEMATICS
HIGH SCHOOL

The proceeds are $?

Answer:

Answer:

The interest is $29.97

The proceeds are $719.28

Step-by-step explanation:

Data:

L = Loan = $749.25

r = Interest rate = 12% = 0.12

t = Time = 120 days

n = days of the year = 360 days

X = Interest in dollars = ?

Y = Proceeds = ?

X =L * t * (r/n) = $749.25 * 120 * (0.12/360) = $29.97

Y = L - X = $749.25 - $29.97 = $719.28

Therefore,

The interest is $29.97

The proceeds are $719.28

Hope this helps!

Answer: Dived loan and purchase to get interest

MIDDLE SCHOOL

29 7/8 divided by 2? What is the answer to this fraction equation?

The fraction 29 7/8 is equal to 14.94.

Here, simplified form of 29 7/8 ÷ 2to be determine.

To perform as the operators present in the numerical.

Here, 29 7/8 ÷ 2

= 236+7/8*2

= 29.346/2

= 14.94

Thus, the fraction 29 7/8 is equal to 14.94.

Learn more about simplification here:

brainly.com/question/12501526

#SPJ2

Answer:

14.9375

Step-by-step explanation:

29 7/8=239/8

(239/8)/2=(239/8)(1/2)=239/16

HIGH SCHOOL

What equation results from completing the square and then factoring? x2 + 6x = 13

Step 1: Subtract 13 from both sides.

x^2+6x−13=13−13x^2+6x−13=0

Step 2: Use quadratic formula with a=1, b=6, c=-13.

x=−b±√b2−4ac2ax=−(6)±√(6)2−4(1)(−13)2(1)

x=−6±√882

x=−3+√22 or x=−3−√22

Answer would be

x=−3+√22 or x=−3−√22

x^2+6x−13=13−13x^2+6x−13=0

Step 2: Use quadratic formula with a=1, b=6, c=-13.

x=−b±√b2−4ac2ax=−(6)±√(6)2−4(1)(−13)2(1)

x=−6±√882

x=−3+√22 or x=−3−√22

Answer would be

x=−3+√22 or x=−3−√22

MIDDLE SCHOOL

Two lines that intersect have _____ solutions

Two lines that intersect have 1 solution

HIGH SCHOOL

Simplify p(p - q) - q(q - p). p 2 - q 2 p 2 + q 2 p 2 + pq - q 2 p 2 - pq - q 2

Answer:

The solution of the expression is

Step-by-step explanation:

Given : Expression

To find : Simplify the expression?

Solution :

Step 1 - Write the expression,

Step 2 - Apply distributive property,

Step 3 - Add like terms,

Therefore, The solution of the expression is

P^2 - pq - q^2 + pq

= p^2 - q^2

= p^2 - q^2